Dimensions Analysis with the Keyword "Islamic Culture" Using Bibliometric Techniques - Khoirunnisa Khoirunnisa; Busro Busro (Gunung Djati Conference Series, 2023)
Studies on Islamic culture continue to be created and published in various disciplines. This study uses data collection and analysis to try to identify trends in Islamic cultural research. This study examines many categories of studies in the fields of research, development, researchers, and places of publication using bibliometric methods on the database dimension. This research has five stages, namely keyword search, data search, article selection, data validation, and data analysis. This study shows that many professionals are still researching and advancing Islamic cultural studies. In the dominant Islamic cultural research category it is studied in the field of Studies in Human Society. The development trend of Islamic cultural research tends to increase from 2014 to 2019 and the highest number occurs in 2020. The most dominant researcher, Moh. Rosyid has published the most articles with a total of 20 articles in his research. Place of publication of research on Islamic culture by the journal Advances in Social Science Education and Humanities Research. The Islamic cultural research presented in this study only uses one database, namely dimensions, so there are still many limitations in the results.